Kajian Beberapa Varietas Unggul Jagung Hibrida dalam Mendukung Peningkatan Produktivitas Jagung - YATI HARYATI; KARSIDI PERMADI (Agrotrop : Journal on Agriculture Science, 2014)
The Assessment of Several Varieties of Superior Hybrid of Maize in Support of An Increase in Productivity of Maize. Maize is one of the commodity that can support industry and exports, therefore an increase of productivity and expansion of planting area is needed and study on varieties of maize that can grow optimally with local area conditions is required. Assessment is done in ‘kelompok tani Lengo’, Sindangkasih village, Sub District Majalengka, District Majalengka, West Java Province from June to August, 2014. It used randomized block design with five varieties of maize hybrids (Bima-3, 4, 5, 6 and 19) and five replications. The aim of the assessment was to determine adaptation of some new varieties of maize hybrids in the local area conditions (specific location). The study showed that with technology of Integrated Crop Management, productivity of Bima-4 variety was highest (8.74 t ha-1) compared to other varieties, indicated that this variety was suitable to be developed in Majalengka. Farming analysis with application of The Integrated Crop Management showed that the the R/C value of Bima-4 variety was 3.48.